Unraveling the complex relationship between night shift work and diabetes: exploring mechanisms and potential interventions - Yuye Zhu; Jing Mi (Frontiers in Public Health, 2025)
It is a topic of increasing concern that the prevalence of night shift work in our 24/7 society is linked to diabetes mellitus. The purpose of this paper is to thoroughly examine existing research on the intricate connection between diabetes and night shift work, with a specific focus on underlying factors including insufficient sleep, disruptions in circadian rhythms, and changes in melatonin levels. Research has shown that the act of working overnight is linked to an increased likelihood of developing type 2 diabetes mellitus (T2DM), despite the fact that the exact reasons for this connection remain unclear. Insufficient sleep and disruption of the natural sleep-wake cycle, which are common consequences of working night shifts, can result in a reduced response to insulin and dysfunctional processing of glucose in the body. Moreover, changes in the production of melatonin, a hormone closely associated with the body's natural sleep-wake cycle, may have a significant impact. Although working the night shift presents numerous difficulties, interventions targeting the enhancement of sleep quality, adjustment of circadian rhythms, and increase in melatonin levels show potential in reducing the risk of developing T2DM. Further studies must persist in exploring these mechanisms and implementing successful tactics to safeguard the wellbeing of shift workers in our current societal context.